2021
DOI: 10.1002/hep.31628
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Ceramidase Mediates Nonalcoholic Steatohepatitis by Regulating Monounsaturated Fatty Acids and Gut IgA+ B Cells

Abstract: Background and Aims Nonalcoholic steatohepatitis (NASH) is associated with obesity and an increased risk for liver cirrhosis and cancer. Neutral ceramidase (NcDase), which is highly expressed in the intestinal brush border of the small intestine, plays a critical role in digesting dietary sphingolipids (ceramide) to regulate the balance of sphingosine and free fatty acids. It remains unresolved whether obesity‐associated alteration of NcDase contributes to the manifestation of NASH. Here, we revealed that NcDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…β-catenin plays an important role in regulation of hepatic glucose and lipid metabo lism. It has been reported that fatty acid treatment will lead to β-catenin accumulation in hepatocytes, which enhances lipogenesis, eventually causing steatohepatitis [33]. Consist ently, under a high fat diet, hepatocyte-specific β-catenin transgenic (TG) mice showed apparent steatosis, as well as rapid obesity and systemic insulin resistance in comparison to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin plays an important role in regulation of hepatic glucose and lipid metabo lism. It has been reported that fatty acid treatment will lead to β-catenin accumulation in hepatocytes, which enhances lipogenesis, eventually causing steatohepatitis [33]. Consist ently, under a high fat diet, hepatocyte-specific β-catenin transgenic (TG) mice showed apparent steatosis, as well as rapid obesity and systemic insulin resistance in comparison to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fecal sphingosine was negatively correlated with the abundance of Desulfovibrio , which suggesting the close relationship between Desulfovibrio and sphingolipid metabolism. It was also reported that the deficiency of neutral ceramidase (NcDase), which was the key enzyme of sphingolipid metabolism and highly expressed in the small intestine and colon, could result in reduction of Desulfovibrio 49 . Streptococcus is one of bacteria which producing d ‐lactic acid in the gut, 50 and was reported increased significantly in the fecal samples of CFS patients 51 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the deficiency of neutral ceramidase (NcDase), which was the key enzyme of sphingolipid metabolism and highly expressed in the small intestine and colon, could result in reduction of Desulfovibrio. 49 Streptococcus is one of bacteria which producing D-lactic acid in the gut, 50 and was reported increased significantly in the fecal samples of CFS patients. 51 In this study, the abundance of Streptococcus was reduced in the high group, suggesting ACJ could suppress the LA production to increase exercise endurance.…”
Section: Alterations Of the Intestinal Microbiota Abundancementioning
confidence: 99%
“…Stearoyl-CoA desaturase 1 (SCD1) is also a key enzyme for hepatic lipid anabolism that catalyzes the rate-limiting step of converting saturated fatty acids into monounsaturated fatty acids (63). Studies have indicated that SCD1 is overexpressed in activated HSCs, and is involved in diet-induced steatohepatitis and fibrosis by regulating Wnt signaling (64,65). Decreasing SCD1 expression through genetic disruption or pharmacological inhibition reduced HSCs activation and alleviated liver fibrosis and steatohepatitis in murine models (66,67).…”
Section: Stearoyl-coa Desaturase 1 and Scd1 Inhibitorsmentioning
confidence: 99%